(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
Number of studies conducted to investigate relationships between corporate sustainability, corporate social responsibility and corporate performance. This research has examined the impact of CSR activities and organizational performance in presence of organizational culture. This was an exploratory research based on primary and secondary data. The primary data of employees of banks collected while secondary data were collected from articles, reports and website of the corporation. The data were analyzed using correlation, regression and analysis of variance by SPSS version 16. The study found relationship between awareness of corporate social responsibility activities and organizational performance. In addition, the study found relationship between organizational culture and organizational performance for the banking sector of Pakistan. The results of this study are important for companies and future research on corporate social responsibility and employee performance.